Waqf (endowment) practice in Malaysian society - Nur Khalidah Dahlan; Noor Inayah Yaa'kub; Mohamad Abdul Hamid; Mohd Rizal Palil (Universiti Kebangsaan Malaysia, 2014)
Justice and equality are not identical in the sense that under certain circumstances, justice may only be achieved through inequality or unequal distribution of wealth. The two aspects of justice, which are corrective justice and distributive justice in this definition both comprehend of justice as a social concept as it incorporates social relations and would have little meaning if it were to apply to an individual in total isolation from society. Thus by comparing the pertinent literature on jurisdiction of the courts in terms of waqf and judicial decisions, this article seeks to describe the pros and cons of waqf practices and how it reflects justice to the Malaysian society.